Рецензія на книги "Могильник Мамай-Гора" - Мурзін, В.Ю. (Археологія, 2010)
Рецензія на книги: С.И. Андрух, Г.Н. Тощев. Могильник Мамай-Гора. - Кн. I. — Запорожье, 1999. — 230 с.; Кн. II. — Запорожье, 2001. — 282 с.; Кн. III. — Запорожье, 2004. — 198 с.; Кн. IV. — Запорожье, 2009. — 310 с.